The Mode of Delivery and Fetal outcome in Abruptio Placentae - Atiyah, Nadia Ridha; Owaid , Ola Muhsein (Academia Open, 2026)
General Background: Abruptio placentae is the premature separation of the placenta after 20 weeks of gestation and remains a major obstetric emergency associated with substantial maternal and perinatal morbidity and mortality. Specific Background: This condition frequently leads to cesarean delivery, maternal anemia, postpartum hemorrhage, disseminated intravascular coagulation, shock, prematurity, and fetal death. Knowledge Gap: National data on abruptio placentae and its associated delivery patterns and fetal outcomes remain limited in Iraq, particularly in the Kurdistan Region. Aims: This study aimed to determine the prevalence of abruptio placentae and to assess the mode of delivery and fetal outcomes among affected pregnancies in Erbil Maternity Teaching Hospital. Methods: A descriptive cross-sectional study was conducted from August 2019 to January 2020 involving 65 pregnant women diagnosed with abruptio placentae. Results: The prevalence of abruptio placentae was 0.69%. Cesarean section was performed in 73.8% of cases. Maternal complications included anemia (95.4%), postpartum hemorrhage (20.0%), blood transfusion (32.3%), disseminated intravascular coagulation (4.6%), and shock (7.7%). Preterm birth occurred in 36.9% of neonates, and fetal death was recorded in 16.9% of cases. Fetal mortality was significantly associated with advanced maternal age, disseminated intravascular coagulation, maternal shock, and prematurity. Novelty: This study provides updated evidence on abruptio placentae outcomes from a tertiary hospital in Iraqi Kurdistan. Implications: Early recognition and prompt management of abruptio placentae are essential to reduce severe maternal complications and perinatal mortality. Highlights: • Abruptio placentae prevalence at Erbil Maternity Teaching Hospital was 0.69%.• Cesarean section was the predominant delivery approach in nearly three-quarters of cases.• Prematurity, maternal shock, and disseminated intravascular coagulation were linked to fetal death. Keywords: Abruptio Placentae, Cesarean Section, Fetal Mortality, Maternal Complications, Prematurity